Modeling the catarrhal stage of Bordetella pertussis upper respiratory tract infections in mice - Soumana, Illiassou H; Dewan, Kalyan K; Linz, Bodo; Rivera, Israel; Ma, Longhuan; Howard, Laura K; Caulfield, Amanda D; Sedney, Colleen J; Blas-Machado, Uriel; Sebo, Peter; Harvill, Eric T (Disease models & mechanisms, 2022)
Pertussis (whooping cough) is a highly transmissible human respiratory disease caused by Bordetella pertussis, a human-restricted pathogen. Animal models generally involve pneumonic infections induced by depositing large numbers of bacteria in the lungs of mice. These models have informed us about the molecular pathogenesis of pertussis and guided development of vaccines that successfully protect against severe disease. However, they bypass the catarrhal stage of the disease, when bacteria first colonize and initially grow in the upper respiratory tract. This is a critical and highly transmissible stage of the infection that current vaccines do not prevent. Here, we demonstrate a model system in which B. pertussis robustly and persistently infects the nasopharynx of TLR4-deficient mice, inducing localized inflammation, neutrophil recruitment and mucus production as well as persistent shedding and occasional transmission to cage mates. This novel experimental system will allow the study of the contributions of bacterial factors to colonization of and shedding from the nasopharynx, as occurs during the catarrhal stage of pertussis, and interventions that might better control the ongoing circulation of pertussis.
Keywords: Mice; pertusová vakcína; Whooping Cough; Lung; Animals; Pertussis Vaccine; Respiratory Tract Infections; Bordetella pertussis; myši; plíce; zvířata; pertuse; infekce dýchací soustavy